The Lattice Structure of L-Contact Relations - Xueyou Chen (Advances in Fuzzy Systems)
From the point of view of graded truth approach, we define the notion of a contact relation on the collection of all L-sets, discuss the connection to the set of all close, reflexive, and symmetric relations on all L-ultrafilters on X, and investigate the algebraic structure of all L-contact relations.